Pneumopericardium in a child – “halo sign” on chest x-ray: A Case Report - Sadaf, Alina; Rashid, Aqeela; Omer, Sadia (Journal of the Pakistan Medical Association, 2024)
A 5 year old boy with acute lymphoblastic leukemia on chemotherapy presented with chest pain and vomiting for two days after an elective procedure under general anesthesia. His chest x-ray was remarkable for a prominent halo sign, an air gap surrounding the heart indicating a large pneumopericardium. Although the pneumopericardium could not be appreciated on an echocardiogram, the child developed clinical signs of cardiac tamponade. Attempts to evacuate the pneumopericardium were unsuccessful leading to death. Keywords: Pneumopericardium, Halo sign.